Implementation of Breach of Contract in a Real Estate Housing Development Cooperation Agreement - D, Daud; Daulay, Khairil Fahmi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
In a cooperation agreement between a developer and a landowner for real estate housing development, the written contract resulted in a breach of contract (default) that caused losses to the landowner. The focus of this study is to examine the breach of contract and the factors causing it in the housing development cooperation agreement between the landowner and the developer, as well as the consequences of the breach and the legal protection available to the landowner. The research method used is descriptive, with data collected through interviews, documentation, and data analysis. Based on the data analysis, it was found that the landowner suffered several losses due to the developer’s failure to comply with the agreed terms in the real estate housing development cooperation agreement. In the implementation of the agreement, the developer did not fulfill its responsibility to construct all the houses as stipulated in the contract. As a result, the landowner did not receive their entitled rights under the agreement and was unable to reuse the land due to the stalled construction caused by the developer’s cessation of the housing development project. Compensation may be resolved through deliberation or by entering into a new agreement outside the main contract as a form of accountability for the consequences. The implementation of the real estate housing development cooperation agreement between the developer and the landowner does not contradict the principles of contract execution.